Geography of marketing and rural development - Shrivastava, V. K. (Virendra Kumar), 1939- (New Delhi, India : Inter-India Publications, 1987)
With reference to the Tarai region of Uttar Pradesh, India.
Includes bibliographical references (p. [198]-207).
Keywords: Farm produce -- India -- Uttar Pradesh -- Marketing; Rural development -- India -- Uttar Pradesh